2020
DOI: 10.1038/s41375-020-0731-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-generated alloantigen-specific Th9 cells mediate antileukemia cytotoxicity in the absence of graft-versus-host disease

Abstract: Allogeneic bone marrow transplantation (BMT) is a curative therapy for various hematological malignancies, such as leukemias and lymphomas. Donor-derived alloantigenspecific T cells eradicate residual tumor cells, however, these T cells are also responsible for the induction of graftversus-host disease (GVHD). Therefore, one major challenge in BMT is the identification of T-cell subsets provoking antitumor cytotoxicity without causing GVHD. T helper (Th) subsets are programmed into various lineages dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A recent report also showed that an orthogonal receptor with an extracellular domain of the IL-2 receptor and an intracellular domain of the IL-9 receptor increases the antitumor activity of T cells and polarizes them towards a stem cell memory and effector phenotype [ 123 ] ( Figure 3 b). In addition, in a mouse model of leukemia, in vitro polarized Th9 cells for allogenic bone-marrow transplantation achieved tumor eradication without inducing graft-versus-host disease [ 124 ].…”
Section: Th9 Cellsmentioning
confidence: 99%
“…A recent report also showed that an orthogonal receptor with an extracellular domain of the IL-2 receptor and an intracellular domain of the IL-9 receptor increases the antitumor activity of T cells and polarizes them towards a stem cell memory and effector phenotype [ 123 ] ( Figure 3 b). In addition, in a mouse model of leukemia, in vitro polarized Th9 cells for allogenic bone-marrow transplantation achieved tumor eradication without inducing graft-versus-host disease [ 124 ].…”
Section: Th9 Cellsmentioning
confidence: 99%
“…Nevertheless, they can be detected during multiple sclerosis, ulcerative colitis, food allergies, allergic inflammation, asthma, and transplant rejection [ 1 , 6 , 7 ]. Moreover, few studies have confirmed the importance of Th9/IL-9 in organ transplant tolerance [ 8 ]. Therefore, this study aimed to investigate the biological and immunologic characteristics of IL-9, as well as its importance in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Th9 cells, first described about a decade ago, are characterized by the potent secretion of IL‐9, a pleiotropic cytokine with both protective and disease‐inducing effects. Functionally, Th9 cells promote anti‐tumor immunity [3, 4] as well as defense against parasitic infections [5], but have also been associated with the pathogenesis of allergic diseases [6, 7]. The transcription factor network controlling Th9 responses is not yet fully understood, and a master gene regulator has so far not been found, as it has for the other Th subsets [8].…”
Section: Introductionmentioning
confidence: 99%